Paradigma Filosofis Tentang Manusia Dalam Al-Qur’an - Ahmad Aziz Masyhadi; Tasmuji Tasmuji (Journal of Innovative and Creativity, 2025)
Human beings are a fascinating subject to study. This is not only because they are one of the objects of philosophical inquiry but also because, essentially, all events that occur in the universe are related to humans. It is for this reason that a wide variety of opinions and viewpoints have emerged. The philosophical study of humans in the Qur'an is an analysis of the human self from a philosophical perspective. Its aim is to discover the essence of humanity and all matters related to it, using the Qur'an as the primary source for examining religious teachings. Consequently, this writing is intended to contribute to and enrich the treasury of scholarly knowledge, in addition to developing concepts about humankind. The expected benefit of this study is that by clearly understanding the mystery of human existence, it can serve as a foundation for further purifying oneself from blameworthy traits (akhlakul mazmumah) and filling it with noble character (akhlakul karimah), thus becoming a perfect human being (insan kamil).